Penatalaksanaan Holistik Wanita Pralansia Dengan Diabetes Mellitus Tipe II Tidak Terkontrol Melalui Pendekatan Dokter Keluarga - Shafa Inayatullah; Tutik Ernawati; Eko Budi Santoso (MAJORITY, 2021)
Diabetes mellitus needs to be managed comprehensively, including pharmacological and nonpharmacological treatment. The treatment goals, complication prevention, and increased quality of life can be achieved by understanding the disease to build self-awareness to modify lifestyles, both diet, as well physical activity. To identify risk factors, clinical problems, conduct patient management holistically by applying family doctors according to evidence based medicine through a patient centered and family approach. Design study is a case report. The primary data obtained through anamnesis (autoanamnesis), physical examination, and home visits. Secondary data were obtained from the patient's medical record. Mrs. S, 56 years old, with type two diabetes mellitus since 5 years ago, concerns about her worsening disease. Knowledge limitations of the patient's health condition, unhealthy diet, and physical inactivity are the factors causing problems in patient’s family. Holistic and comprehensive management of the problems of Mrs. S has been carried out by providing counseling using posters to increase the knowledge of the patient and the patient's family regarding the patient's diet and the importance of physical exercise, as well as routine control to the nearest health facility. After the evaluation, it was found that the patient’s blood sugar decreased while in patient.